2020
DOI: 10.35308/source.v5i2.1399
|View full text |Cite
|
Sign up to set email alerts
|

Pembingkaian Budaya Jawa Dan Belanda Di Dalam Novel Bumi Manusia

Abstract: The novel Bumi Manusia is a controversial novel that contains Indigenous life in the Dutch colonial period. Pram depicts the cultural differences between Indigenous and Dutch with a very contrast in all aspects in more detail and depth. The purpose of this research is to expose the cultural differences which are framed in the novel Bumi Manusia. This research is also intended to expose the differences between Javanese and Dutch cultures which not only distinguish culture based on appearance and language. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Hybridity of Indies Culture in Indonesian Novel Translation into French cultures and values (Hastuti, 2018;Nasution et al, 2020). However, this article found that Bumi Manusia depicts the other culture, Indies/Indische culture, between the two cultures.…”
Section: Discussionmentioning
confidence: 68%
“…The Hybridity of Indies Culture in Indonesian Novel Translation into French cultures and values (Hastuti, 2018;Nasution et al, 2020). However, this article found that Bumi Manusia depicts the other culture, Indies/Indische culture, between the two cultures.…”
Section: Discussionmentioning
confidence: 68%